A study on energy-efficient train driving in a line with short headway - Naoki OBA; Masafumi MIYATAKE (Nihon Kikai Gakkai ronbunshu, 2019)
Energy-efficient driving is one of the major effective methods to reduce energy consumption of railway system. It has substantial advantage that need much less investment cost than other countermeasures. However, that has not been investigated in detail at short headway situation in rush hours where two trains interact with each other through signaling systems to prevent train collision. In this situation, some trains make unexpected accelerations and decelerations much often to track the preceding train and increase energy loss. Here we show theoretically what driving technique is much better from energy consumption point of view. In the simulation, we examine a technique to drive a train in an energy-efficient way when the preceding train is delayed departing station by simulations. The dynamic programming (DP) is employed to optimize the energy-efficient train speed profile and modified to implement the behavior of fixed-block signaling systems. The sensitivity analysis to change the delay of first train is made to clarify the relation between energy consumption and train delay propagation to the second train. The results show that it can suppress energy consumption less than or equal to regular running time situation.